Students’ Speaking Anxiety at English Classroom in Agroecotechnology Department of Agricultural Faculty Untirta (A Descriptive Study in AgroEcoTechnology Classroom, Untirta) - Ika Handayani; Eri Rahmawati (English Department - University of Sultan Ageng Tirtayasa, 2017)
This writing is a minor report of a descriptive research conducted to know the level of students’ Speaking anxiety at English Classroom in Agroecotechnology Department of Agricultural Faculty, to find out the causes of the students’ speaking anxiety and to describe the students’ strategies in solving the speaking anxiety problems. In this study, method of the research is descriptive qualitative. The data were collected through questionnaire (using Foreign Language Classroom Anxiety Scale that designed by Horwitz et al) and semi structured interview. The researchers chose 2A of Agroecotechnology Class as the subject of this research. Further, the data analysis used in this research done through data reduction, data analysis and data display (qualitatively). To check the credibility of the data (trustworthiness), the researchers used triangulation on technique. The finding of this research would be meaningful contribution for the researchers as the lecturers of English in Agricultural Faculty to apply certain strategy in solving the students’ speaking anxiety problem in joining English class. Keywords: Agroecotechnology department; English classroom; Speaking Anxiety;